2019
DOI: 10.1111/bju.14834
|View full text |Cite
|
Sign up to set email alerts
|

New basic insights on the potential of a chitosan‐based medical device for improving functional recovery after radical prostatectomy

Abstract: L.M. and F.F. contributed equally to this work ConclusionThe results of this study provide the first experimental evidence in support of the clinical safety of CS-Me and of their postulated effectiveness for improving functional recovery after RP. The presented results are coherent in demonstrating that acutely axotomised autonomic neurones show increased neurite outgrowth on CS-Me substrate, whilst the same substrate reduces prostate cancer cell line proliferation in vitro. Furthermore, CS-Me do not demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…22 The same group also assessed the functional characteristics of the chitosan membrane, including neurogenerative effect, modifying effect, and tissue reaction using the preclinical models. 23 In the study, they confirmed that the functional effects of an implanted material using a grasping test of a rat median nerve model. 23 In contrast, we successfully developed the cavernous nerve damage model in a rat and confirmed the effectiveness of ALG with PGA mesh in restoring the erectile function after cavernous nerve excision, suggesting that the efficacy of our novel material in enhancing the autonomic nerve regeneration along with somatic nerve regeneration.…”
Section: Discussionsupporting
confidence: 52%
“…22 The same group also assessed the functional characteristics of the chitosan membrane, including neurogenerative effect, modifying effect, and tissue reaction using the preclinical models. 23 In the study, they confirmed that the functional effects of an implanted material using a grasping test of a rat median nerve model. 23 In contrast, we successfully developed the cavernous nerve damage model in a rat and confirmed the effectiveness of ALG with PGA mesh in restoring the erectile function after cavernous nerve excision, suggesting that the efficacy of our novel material in enhancing the autonomic nerve regeneration along with somatic nerve regeneration.…”
Section: Discussionsupporting
confidence: 52%
“…These studies validated SilkBringe TM , safety and its beneficial effect on median nerve recovery [ 80 , 81 ]. These groups are specialized in nerve tissue engineering and regeneration: they have produced several works on decellularized nerve grafts [ 82 ], neuronal grafts conduits based on synthetic biomaterials (PLC and polyhydroxyalkanoates) [ 83 , 84 ], and other nerve regeneration techniques [ 85 , 86 ].…”
Section: Application Fieldsmentioning
confidence: 99%